Synergistic Effect of Polyethylene Oxide Layer on TiO2/TiO2-Graphene based Perovskite Solar Cell - Gaur, Deepika; Sharma, Sunita; Ghoshal, S.K.; Seth, Pooja; Aggarwal, Shruti; Aggarwal, Neha (Asian Journal of Chemistry, 2020)
This article reports the influence of titania (TiO2) and TiO2-graphene (TGr) as electron transport layer (ETL) on the performance of polyethylene oxide (PEO) based perovskite solar cell (PSC). Compared to most commonly used ETLs, graphene based ETLs showed immense promise towards scalable fabrication and higher carrier injection of PSC. Driven by this idea, PEO layer was introduced in TiO2 and TGr based PSC to inspect the feasibility of achieving notably high fill factor. As-grown nanocomposites were analyzed using varied analytical tools to determine the effect of graphene inclusion on their morphology, optical and electrical properties. An increase in the absorption bandwidth and red-shift in the absorption peak was observed from UV-VIS spectra indicating band gap narrowing. By exploiting TGr nanocomposite in perovskite solar cells as electron collection layer, a remarkable fill factor of 44% has been achieved. In short, present disclosure may contribute towards the development of ETL in high performing PEO based perovskite solar cell (PSC).